2005
DOI: 10.1103/physreve.71.026231
|View full text |Cite
|
Sign up to set email alerts
|

Limits on the excitable behavior of a semiconductor laser with optical feedback

Abstract: Recently, it was proposed that semiconductor lasers with optical feedback present a complex behavior that can be described as noise driven excitable. In this work we investigate in which region of parameter space this description is adequate. We conclude that the region of the parameter space in which the system displays noise driven excitable behavior is a subset of the region in which presents low frequency fluctuations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…4 for the present system for α = 3.2 and 5 and µ = 0.93, in both cases two stable attracting modes have been identified. Recently, a similar coexistence of two stable solutions located in proximity of the MGM has been reported experimentally for an edge-emitter laser with a low level of optical feedback [40] As reported in [37] the stability properties of the MGM do not depend on α, therefore it is reasonable to expect that some SM will be always present in a narrow window around θ for any chosen linewidth enhancement factor [39] and that they will coexist with the chaotic dynamics, as observed experimentally in [41]. The ECMs with θ < θ1 are modes, while the others are antimodes.…”
Section: Stationary Solutionssupporting
confidence: 63%
“…4 for the present system for α = 3.2 and 5 and µ = 0.93, in both cases two stable attracting modes have been identified. Recently, a similar coexistence of two stable solutions located in proximity of the MGM has been reported experimentally for an edge-emitter laser with a low level of optical feedback [40] As reported in [37] the stability properties of the MGM do not depend on α, therefore it is reasonable to expect that some SM will be always present in a narrow window around θ for any chosen linewidth enhancement factor [39] and that they will coexist with the chaotic dynamics, as observed experimentally in [41]. The ECMs with θ < θ1 are modes, while the others are antimodes.…”
Section: Stationary Solutionssupporting
confidence: 63%
“…1(a)]. The motivation for this classification is that some dropouts can be noise-induced while others can be due to a deterministic underlying dynamics303132. Thus, some IDIs correspond to waiting intervals in a resting state until noise triggers a dropout, while others correspond to time intervals between dropouts that are more likely to have a deterministic origin.…”
mentioning
confidence: 99%
“…Moreover, in [28] the periodic "spike" patterns generated experimentally under external periodic forcing were compared with the solutions of the EGM model, and it was shown that the topological organization of the experimentally observed periodic orbits was equivalent, in the parameter region explored, to the one displayed by the model solutions. The limits of the excitable LFF behavior, and thus the region of validity of the EMG model, were studied in [29], where it was shown that excitability deteriorates in the parameter region where there is a high probability of stable emission; in this region of "coexistence" the laser dynamics can be separated into stable and bursting states.…”
Section: Introductionmentioning
confidence: 99%